Philosophical Reconstruction of the Concept of "Restoration of the Original State" in Article 79 Paragraph (1) of Law Number 20 of 2025 concerning the Criminal Procedure Code - Andrea Hynan Poeloengan; Zulkarnain Koto; Ismail Koto (Jurnal Hukum Replik, 2026)
The development of the global criminal justice system shows a paradigm shift from retributive justice to restorative justice, which places restoration as the primary orientation in resolving criminal cases. In the Indonesian context, restorative values have been alive in the tradition of customary law and the philosophy of Pancasila, but were marginalized by colonial legal formalism. Legal reform through the New Criminal Procedure Code, specifically Article 79 paragraph (1) of Law Number 20 of 2025, reintroduces the concept of "restoring the original state" as an instrument for protecting human rights and substantive justice. The problem is, without a philosophical reconstruction based on Pancasila values, the concept of restoration has the potential to be reduced to a material compensation mechanism that opens up space for the practice of "transactions of impunity" and inequality in social justice. This research uses a normative juridical method with an approach to vertical and horizontal synchronization of legal norms and is reinforced by scenario planning within a foresight method framework to project the implications of the application of norms in a reductive manner. The research findings indicate that restoration to the original state must be interpreted as a multidimensional process encompassing the restoration of human dignity, social relational balance, and the state's responsibility to protect citizens' rights. A Pancasila-based philosophical reconstruction is necessary for the concept of restoration to function as an authentic instrument of restorative justice in the modern Indonesian criminal justice system. Keywords: Philosophical Reconstruction, Restoration of the Original State, Article 79 Paragraph (1) of LawNumber 20 of 2025.